View of the open space in front of the club - Mumbai Archive Project (Jio Institute, 2024)
The view of the open space in front of the club is reserved for parking vehicles (as mentioned on the board above the entrance). The quarters above the entrance are used by members of the club who currently live there. Interestingly, this space was once used as the servants' quarters. Nowadays, the club cannot afford to have servants.